From pathogenesis to clinical practice: Emerging medical treatments for endometriosis. (August 2018) - Clemenza, Sara; Sorbi, Flavia; Noci, Ivo; Capezzuoli, Tommaso; Turrini, Irene; Carriero, Carlo; Buffi, Nicolò; Fambrini, Massimiliano; Petraglia, Felice
Abstract: Endometriosis is a chronic disease, and a lifelong management plan should be developed by using pharmacological treatment and surgical procedures. The pathogenesis of endometriosis is complicated and has not been definitively established. The mechanisms involved are numerous, and their understanding is constantly evolving. Currently, the first-line drugs act by blocking ovarian function, creating an hypoestrogenic environment. The blockade of estrogen secretion and receptor activity and the activation of progesteron receptors are the main target of several current drugs, as well as those under development. The oral GnRH antogonists, the aromatase inhibitors, SERMs, and SPRMs are the hormonal drugs currently studied for treating endometriosis. The increasing knowledge of the pathogenesis has allowed the development of new treatments. The most studied are the anti-inflammatory drugs, starting from the new NSAIDs to the monoclonal antibodies and the statins. Among the antiangiogenic compounds, a role is suggested for Icon, PPARs, and HDACIs. A new class of drugs is the cannabinoids. The aim of this review was to investigate the new therapeutic hormonal and non-hormonal alternatives to standard treatments. Highlights: The pathogenesis of endometriosis has not been definitively established. The increasing knowledge of the pathogenesis has allowed the development of new treatments. The emerging medical treatments for endometriosis include hormonal drugs and non-hormonal drugs.